SISTEM PENDATAAN AGROEKOSISTEM LAHAN PERTANIAN DENGAN KOMODITAS PADI IRIGASI, JAGUNG, DAN UBI KAYU - Kusumah, Fitrah Satrya Fajar; Riana, Freza (Krea-TIF: Jurnal Teknik Informatika, 2017)
Land suitability information on food crops is very important to know that can produce healthy food food, economical, and sustainable. In connection with the foregoing matters and for the implementation of article 22 of Government Regulation No. 12 of 2012 on Sustainable Agricultural Land Protection, it is necessary to stipulate the Land Conformity Guidance on Food Crop Commodities. The Land Suitability Guidance on Commodities of Food Crops is a mandate from Article 22 of Government Regulation No. 12 of 2012 on Sustainable Land Sustainability of Food Agriculture as outlined in the Regulation of the Minister of Agriculture. Application of Land Suitability of Crop Plants form of land suitability of food crops that provides convenience in terms of data collection of agricultural areas throughout Indonesia and can be run on a national scale with a focus on food crops such as: irrigated rice paddy; Gogo rice; Corn; Peanuts; Soy; Cassava; Sweet potato. This application can be done in web form. Through this application is expected local government in this case the provincial government can answer the areas of agriculture at the municipal government level.